Selection of 3PL Vendors for The Distribution of Garment Products Using The ANP: A Case at An Indonesia Garment Company - Wafi Hudaya; Anggi Widya Purnama; Syafrianita Syafrianita (Jurnal Logistik Indonesia, 2025)
Decision-making for the selection of a 3PL vendor needs to look at many factors, currently PT BASIL has not determined a vendor for the new delivery route as well as previously the selection of a vendor based on price and fleet availability. This study uses the Analytical Network Process (ANP) method assisted by super decision which provides value information in the form of weight, alternatives that have high weight are recommended recommendations. The results of data processing from the highest order for the criteria are delivery 19%, service 16%, experience 15%, quality 14%, responsive 12%, performance 11%, insurance 7%, price 5%. For the sub-criteria, namely the reputation of the vendor, the availability of the car carrier when there is demand and the ability to fulfill the specified schedule when there is a demand 12.50%, the safety of goods 7.54%, payment 6.48%, good complaint handling 6.39%, low price 6.02%, the condition of the goods 4.96%, good communication 4.84%, liability 4.80%, late goods insurance 4.75%, damaged goods insurance 4.26%, flexible 4.24%, lost goods insurance 3.49%, punctuality 3.06%, ability to respond to defective and surviving goods claims 2.86%, non-defective goods 2.11%, accuracy of the quantity of units delivered and units received in good condition 2.10%, goods not lost 2.01%, fleet condition 1.40%, accurate 1.12%, documents 0.48%, paying attention to K3 in operational activities 0%. For the alternative with the highest weight, Lion Parcel is 36%, because Lion Parcel is a vendor that matches the priority needs of the company.